2006
DOI: 10.1037/0894-4105.20.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Early patterns of verbal memory impairment in children treated for medulloblastoma.

Abstract: Children treated for medulloblastoma demonstrate a variety of cognitive deficits in addition to white matter and hippocampal neuropathology. This study examined 40 children treated for medulloblastoma as compared with 40 demographically matched controls on the California Verbal Learning Test-Children's Version (D. C. Delis, J. H. Kramer, E. Kaplan, & B. A. Ober, 1994). Results revealed significantly poorer performance on indices of word recall in the patient group as compared with the controls in addition to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 43 publications
(58 reference statements)
2
55
0
1
Order By: Relevance
“…Intellectual and academic outcomes are considered distal markers that arise secondary to changes in underlying core cognitive skills (Mulhern and Palmer 2003;Palmer et al 2003;Palmer et al 2007). Impairments in foundational skills of broad memory, working memory, attention and information processing speed have also been reported (Dennis et al 1998;Kieffer-Renaux et al 2000;Mabbott et al 2008;Mulhern et al 2004;Nagel et al 2006;Reeves et al 2006;Schatz et al 2000;Spiegler et al 2004) and may be precursors to the observed declines in intellectual function and academic function.…”
Section: Core Cognitive Abilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Intellectual and academic outcomes are considered distal markers that arise secondary to changes in underlying core cognitive skills (Mulhern and Palmer 2003;Palmer et al 2003;Palmer et al 2007). Impairments in foundational skills of broad memory, working memory, attention and information processing speed have also been reported (Dennis et al 1998;Kieffer-Renaux et al 2000;Mabbott et al 2008;Mulhern et al 2004;Nagel et al 2006;Reeves et al 2006;Schatz et al 2000;Spiegler et al 2004) and may be precursors to the observed declines in intellectual function and academic function.…”
Section: Core Cognitive Abilitiesmentioning
confidence: 99%
“…Accommodations within school environment may also reduce the impact on academic performance and facilitate rehabilitation (Butler and Haser 2006;Butler and Mulhern 2005;Nagel et al 2006;Palmer and Leigh in press;Palmer et al 2007). Slowed processing speed will require extended time for completing assignments, homework and tests.…”
Section: Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Recent studies have also revealed that children treated for medulloblastoma experience deficits in more key cognitive skills. [4][5][6][7][8][9][10] A retrospective examination of 70 patients treated for a brain tumor found deficits in speed of processing, attention, memory, and academic performance at approximately 3 to 4 years after diagnosis. 4 A study of cognitive skills among a group of survivors of pediatric leukemia and brain tumor found that treatment with cranial irradiation was associated with slowed information processing and difficulties with working memory (WM).…”
Section: Introductionmentioning
confidence: 99%
“…Istraživanje Palmera je pokazalo da deca sa meduloblastomom koja su razvila sindrom cerebelarnog mituzma kao posledicu hirurške resekcije tumora, imaju značajno lošija postignuća u merenju pažnje, brzini procesiranja, radnoj memoriji, egzekutivnim funkcijama i akademskim veštinama 12 meseci nakon postavljanja dijagnoze sindroma mutizma [26,30,31]. Deca i mladi, lečeni od tumora CNS-a pokazuju neurokognitivne deficite koji se ispoljavaju u ključnim kognitivnim funkcijama uključujuči radnu memoriju [32], egzekutivne funkcije [29,[32][33][34][35][36][37], brzinu procesiranja [36], verbalnu memoriju [37] i pažnju i pamćenje [38][39][40]. Različite studije su takođe pokazale slične deficite u verbalnom pamćenju, korišćenju jezika i verbalizaciji, vizuo-spacijalnim veštinama i pažnji [10,16].…”
Section: Neurokognitivne Posledice Tumora Cns-a Kod Dece I Mladihunclassified